Labor market dynamics in Tunisia: The issue of youth unemployment - Marco Stampini; Audrey Verdier-Chouchane (Institute for the Study of Labor (IZA), 2011)
This paper analyzes the dynamics of the youth labor market in Tunisia using unique labor force survey data from 2005 to 2007 that include a longitudinal component. It first shows that sustained economic growth will reduce youth unemployment over the next few years. Second, forecasts indicate that the growth of private sector services has the highest potential to reduce youth unemployment. Third, the analysis of labor market characteristics reveals that young graduates experience long unemployment as they cue for high-skill jobs. Moreover, the public sector remains the main provider of employment opportunities for many graduates, in particular for women.
urn:nbn:de:101:1-201104134525
Keywords: J21; J64; J68; J71; 330; labor market; unemployment; youth; Tunisia; Jugendarbeitslosigkeit; Junge Arbeitskräfte; Wirtschaftswachstum; Beschäftigungseffekt; Tunesien